Strategi Peningkatan Kualitas Produksi Minyak Kelapa Menjadi VCO Dengan Teknologi Penyaringan Bertingkat di Desa Ban, Karangasem-Bali - I Gede Kariasa; I Wayan Swastika; I Nengah Muliarta (Institut Nalanda, 2023)
The community engagement program in the village of Ban, Karangasem-Bali, is focused on improving the quality of Virgin Coconut Oil (VCO) production, which has traditionally relied on conventional technology. Embracing a community-based approach, this program introduces tiered filtration technology as an innovative solution in the VCO production process. Through a series of activities such as surveys, socialization, demonstrations, and monitoring and evaluation (M&E), the residents of Ban Village receive training and information related to this technology. Throughout the community engagement process, it becomes evident that the introduction of tiered filtration technology has successfully increased the community's interest in producing VCO. The community gains better knowledge about the VCO production process, enhances their skills, and boosts their confidence in adopting this new technology. Furthermore, VCO produced using tiered filtration technology exhibits significant improvements in quality, marketability, and shelf life compared to the conventional methods previously used. As a result, VCO production in Ban Village experiences growth, contributing to the improvement of the local economy and enhancing the well-being of the community. Moreover, the production of high-quality VCO also encourages the promotion of this local product in both local and regional markets. Therefore, this effort not only impacts the enhancement of VCO production quality but also plays a crucial role in advancing rural communities and promoting high-quality VCO products in broader markets.